Nghiên cứu đặc điểm sự hấp phụ của 2,4-dinitrotoluen trên một số loại than hoạt tính trong môi trường nước - Thiệp, Tô Văn; Mai, Vũ Thị Hoàng; Khuê, Đỗ Ngọc; Loan, Đồng Kim; Hoàng, Nguyễn Văn; Minh, Đỗ Bình; Tuấn, Nguyễn Cao (Vietnam Journal of Chemistry, 2012)
This research investigates the absorptive characteristics of several types of activated carbon to 2, 4- dinitrotoluene (DNT) and 2,4-dinitrophenol (DNP) on different range of concentration following Freundlich adsorption law. Dedicated coals used to bleach color in water such as TQ and TM are able to absorb DNT well. However, concerning DNP, TQ coal is likely to be the only material that can absorb DNP well from water.